Aljamiado Hispanofilipino The Spanish Language in Philippine Jawi Script - Donoso, Isaac (2018)
From the seventeenth century to the nineteenth century PhilippineMoros increasingly wrote the Spanish language in Arabic script known as Philippine Jawi. This cultural phenomenon, which went beyond merecode switching, is illustrated through documents found in the NationalArchives of the Philippines, particularly protocols involving the Tausug and Maguindanao sultanates. The use of Spanish in Jawi documents increased,thanks to Zamboanga’s role as a cultural center in the south and Manila’s ability to attract sultans politically. Jawi was also used as the scriptin language primers through the strategic work of the Jesuit Jacinto Juanmartí, who originated Moro philology
Keywords: Arabic language; Spanish language; Jawi alphabet; Philology; Juanmarti, Jacinto, 1833-1897